Pengaruh Citra Merek dan Kualitas Produk Terhadap Keputusan Pembelian dengan Kepercayaan Konsumen sebagai Variabel Mediasi Studi pada Konsumen Belikopi di Kota Yogyakarta - Amelia Jelita Putri; Muhammad Mathori (HK Publishing, 2025)
This study aims to analyze the influence of brand image and product quality on purchasing decisions with consumer trust as a mediating variable among Belikopi consumers in Yogyakarta City. This study uses a quantitative approach with a purposive sampling technique. Data were collected through distributing questionnaires to 113 respondents who met certain criteria. Data analysis used the Partial Least Squares Structural Equation Modeling (SEM-PLS) method with the help of SmartPLS software version 3.2.9. The results show that brand image and product quality have a positive and significant effect on consumer trust and purchasing decisions. Consumer trust has a positive and significant effect on purchasing decisions and mediates the relationship between brand image and purchasing decisions. However, consumer trust does not significantly mediate the relationship between product quality and purchasing decisions. Keywords: Brand Image, Product Quality, Consumer Trust, Purchase Decision.